AngelChik Device Removal and Revisional Fundoplication: Lessons from the Past and Thoughts for the Future - Chase, Hannah; Mastoridis, Sotiris; Maynard, Nicholas (Journal of the Nuffield Department of Surgical Sciences, 2021)
Gastro-oesophageal reflux disease (GORD) is a common condition in developed countries with an increasing incidence in the UK, currently estimated at 5 per 1000 person-years. Risk factors for GORD include Helicobacter pylori infection, obesity, alcohol consumption, smoking and genetic predisposition. Surgical management is performed in chronic, severe cases of GORD, refractory to medical management. There are a variety of interventional surgical techniques available and the patient in this case had placement of an AngelChik Device (AD) 30 years ago. This is now a historic device due to associated complications and this patient had it removed with revisional treatment of the patient’s GORD with Nissen Fundoplication. The patient experienced multiple post-surgical complications, namely biliary leak from the central port, pulmonary embolism and pneumonia. Following description of the case, this report will discuss the increasing incidence of late complications of AD and propose a proactive approach to these patients going forwards. It will also discuss the current uncertain evidence of a new surgical intervention called magnetic sphincter augmentation (MSA) of the lower oesophagus that has similar principles to the mechanism of an AD. From this it will emphasise that more stringent and worldwide collaboration is required when bringing a new medical device into clinical care.